The Impact Of Motivation And Work Ethic On The Performance Of The Hkbp Tanjung Karang Church Council - Sirait, Miduk; Ariswandy, David (Universitas Dehasen Bengkulu, 2025)
The performance of the HKBP Tanjung Karang Church Council members is crucial in supporting the church's vision and mission, yet it is still affected by suboptimal motivation and work ethic. Data indicate a high level of absenteeism and tardiness, reflecting low motivation. Although most work programs have been implemented, performance outcomes have not met the expected targets. This study aims to analyze the impact of motivation and work ethic on the performance of Church Council members, with the hope of providing recommendations to improve the performance and effectiveness of the church organization. The research will be conducted at HKBP Tanjung Karang from June to July 2024 using a descriptive quantitative approach, aiming to present factual and accurate information about a specific population. Field research methods will be used, with all 35 council members serving as the sample, making this a population study. The variables investigated include the independent variables, Motivation (X1) and Work Ethic (X2), and the dependent variable, Church Council Performance (Y). A Likert-scale questionnaire will be used as the data collection instrument. Quantitative analysis results show that Motivation (X1) influences Church Council Performance (Y) by 59.5%, while Work Ethic (X2) influences it by 61.2%. Simultaneously, these two variables impact Church Council Performance at HKBP Tanjung Karang by 60.5%, with the remainder influenced by other variables not examined in this study.